The Decline and Persistence of the Old Boy: Private Schools and Elite Recruitment 1897 to 2016 - Reeves, Aaron; Friedman, Sam; Rahal, Charles; Flemmen, Magne (American Sociological Review, 2017)
We draw on 120 years of biographical data ( N = 120,764) contained within Who’s Who—a unique catalogue of the British elite—to explore the changing relationship between elite schools and elite recruitment. We find that the propulsive power of Britain’s public schools has diminished significantly over time. This is driven in part by the wane of military and religious elites, and the rise of women in the labor force. However, the most dramatic declines followed key educational reforms that increased access to the credentials needed to access elite trajectories, while also standardizing and differentiating them. Notwithstanding these changes, public schools remain extraordinarily powerful channels of elite formation. Even today, the alumni of the nine Clarendon schools are 94 times more likely to reach the British elite than are those who attended any other school. Alumni of elite schools also retain a striking capacity to enter the elite even without passing through other prestigious institutions, such as Oxford, Cambridge, or private members clubs. Our analysis not only points to the dogged persistence of the “old boy,” but also underlines the theoretical importance of reviving and refining the study of elite recruitment.